Reviews (Blackfriars, 1958)
Book reviewed in this article: Modern Miraculous Cures By François Leuret and Dr Henri Bon. The Background of the New Testment and Its Eschatology. Studies in Honour of C.H. Dodd. Early Bible Iillustrations. By James Strachan. A Popula History of The Reformation. By Philip Hughes. William Harvey: His Life and Times; His Discoveries; His Methods. By Louis Chauvois. The Poetry of Living Japan. A Anthology with an Introduction by Takamichi Ninomiya and D. J. Enright. Saint Augustine and his Influence Through the Ages. By H-I. Marrou. Rimbaud. By C. A. Hackett.